The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1098/rspb.1998.0311
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a cDNA encoding a potential morphogen from the marine sponge Geodia cydonium, that is conserved in higher Metazoans

Abstract: Species belonging to the lowest metazoan phylum, the sponges (Porifera), exhibit a surprisingly complex and multifaceted Bauplan (body plan). Recently, key molecules have been isolated from sponges which demonstrate that the cells of these animals are provided with characteristic metazoan adhesion and signal transduction molecules, allowing tissue formation. In order to understand which factors control the spatial organization of these cells in the sponge body plan, we screened for a cDNA encoding a soluble mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…10 In line with these studies it could be clarified, mainly from results with the marine sponges Suberites domuncula and Geodia cydonium, that Porifera have molecules similar to those known from the mammalian innate immune system, such as molecules containing scavenger receptor cysteine-rich domains, 11,12 cytokine-like molecules 13 or members of the (2'-5')oligoadenylate pathway. 14 ± 16 Furthermore, it could also be shown that`precursors' of the second type of immune response in mammals, the adaptive immune system, are present in sponges.…”
Section: Introductionmentioning
confidence: 51%
“…10 In line with these studies it could be clarified, mainly from results with the marine sponges Suberites domuncula and Geodia cydonium, that Porifera have molecules similar to those known from the mammalian innate immune system, such as molecules containing scavenger receptor cysteine-rich domains, 11,12 cytokine-like molecules 13 or members of the (2'-5')oligoadenylate pathway. 14 ± 16 Furthermore, it could also be shown that`precursors' of the second type of immune response in mammals, the adaptive immune system, are present in sponges.…”
Section: Introductionmentioning
confidence: 51%
“…Their expression is upregulated during fusion and rejection reactions. Among them are the allograft inflammatory factor, the (2Ј-5Ј)oligoadenylate synthetase , and a potential morphogen (Pahler et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…At present it can be postulated that the an (2′-5′)A system is involved in a cytokine-mediated pathway and/or in the protection system against viruses, present in the marine environment. The existence of cytokines or related molecules has been shown in sponges [14] and the presence of viruses in the marine milieu is well documented [56]. Studies are in progress to identify further components of the (2′-5′)A system in sponges and to elucidate the structure of the sponge (2′-5′)A synthetase gene(s).…”
Section: Discussionmentioning
confidence: 99%
“…integrin receptor [2], collagen [3] or galectin [4,5]), cell-surface receptors (tyrosine kinase receptor [6]), elements of the sensory system (crystallin [7], metabotropic glutamate receptor [8]) and homologs/modules of an immune system (immunoglobulin-like domains [9], scavenger receptor cysteine-rich domains and short consensus repeats [10], Rh-like protein [11]). These molecules were found to display high similarity to sequences from members of higher metazoan phyla [12].Recently a cDNA encoding a putative cytokine, the endothelial monocyte-activating polypeptide [13], was identified in G. cydonium [14]. The physiological role of this factor in sponges is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation